2021
DOI: 10.46419/vs.52.2.10
|View full text |Cite
|
Sign up to set email alerts
|

Antimikrobna osjetljivost uzročnika mastitisa krava s područja sjeverozapadne Hrvatske u razdoblju od 2014. do 2018. godine

Abstract: U ovom su radu prikazani rezultati mikrobioloških pretraga sekreta vimena krava s različitim oblicima upala mliječnih žlijezda. Pretraženi su uzorci tijekom pet godina dostavljani u Laboratorij za dijagnostiku Veterinarskog zavoda Križevci, podrijetlom iz 7 županija sjeverozapadne Hrvatske. Uzorci su pretraženi konvencionalnim mikrobiološkim metodama u aerobnim uvjetima. Ukupno je obrađeno 1264 uzorka, a pozitivan rezultat ustvrđen je u 983 slučaja ili 77,76 % uzoraka. Pri tome je izdvojeno 967 sojev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A prolonged course of treatment and dosage adjustment is required. Other studies have reported evidence of quinolone resistance in China [46], Croatia [57], and Slovakia [58]. However, it is important to note that quinolone resistance is acquired through the accumulation of various resistance mechanisms within a single bacterial strain and can be transferred to others [59].…”
Section: Discussionmentioning
confidence: 99%
“…A prolonged course of treatment and dosage adjustment is required. Other studies have reported evidence of quinolone resistance in China [46], Croatia [57], and Slovakia [58]. However, it is important to note that quinolone resistance is acquired through the accumulation of various resistance mechanisms within a single bacterial strain and can be transferred to others [59].…”
Section: Discussionmentioning
confidence: 99%